Pemberdayaan Masyarakat melalui Optimalisasi Pengolahan Sampah Organik Metode Simple Dekomposer bagi Masyarakat - Desmon Katiandagho; Jane Anita Kolompoy; Yanny Karundeng (CV. CENDIKIA JENIUS INDONESIA, 2026)
Suboptimal organic waste management in Kiawa II Village, North Kawangkoan District, Minahasa Regency, has contributed to environmental pollution due to the improper disposal of agricultural and household organic waste. This community service program aimed to improve community knowledge and skills in managing organic waste through the Simple Decomposer method. The program consisted of an initial survey, coordination with the village government and environmental health officers, educational sessions, demonstrations of decomposer construction, and hands-on assistance in applying the Simple Decomposer using Black Soldier Fly (Hermetia illucens) larvae. The participants were residents of Kiawa II Village, most of whom were vegetable farmers. The program improved participants' understanding of organic waste management and resulted in the construction of 10 Simple Decomposer units installed in participants' homes and one demonstration unit at the village office. The program promoted environmentally friendly waste management practices while supporting household waste reduction and the implementation of a circular economy.